Some indicators of free radical oxidation and antioxidant protection in the erythrocytes of former athletes - A. V. Elikov (National Electronic Information Consortium (NEICON), 2021)
Objective: to study the main indicators of free radical oxidation and antioxidant protection in the erythrocytes of former athletes, depending on the period of termination of sports.Materials and methods: 24 former male athletes aged 19-29 years were examined, who were divided into 2 groups of 12 people each (1st group - former athletes who stopped training for up to 2 years; 2nd - over 2 years). The control group consisted of 15 practically healthy untrained student volunteers of the same age. In erythrocytes, spectrophotometrically (spectrophotometer Shimadzu 1240, Japan), the activity of antioxidant enzymes was determined: superoxide dismutase (SOD) (K.F. 1.15.1.1) - by inhibiting the reduction of nitro blue tetrazolium by superoxide anion radical at λ = 540 nm, after preliminary processing of erythrocytes by the method of Dubinina E.E. and others [8]; catalase (K.F. 1.11.1.6) - according to the rate of utilization of hydrogen peroxide at λ = 260 nm; glutathione peroxidase (HP) (KF 1.11.1.9) - by the change in the content of reduced glutathione in samples before and after incubation of the substrate with dithiobis-nitrobenzoic acid at λ = 412 nm; glutathione reductase (GR) (K.F. 1.6.4.2) - according to the catalytic NADPH ∙ H+-dependent transformation of the oxidized form of glutathione into the reduced form, the intensity of which was estimated by the rate of decrease in the extinction of samples at λ = 340 nm, at which the NADPH H+ solution has a maximum light absorption (Warburg test).Results: the direction of the shifts in the state of the oxidative balance was established depending on the period of detraining. A significantly lower value of the total antioxidant activity was revealed in the former athletes of the 1st group. This phenomenon is probably associated with a decrease in the efficiency of the enzymatic link of the antioxidant defense in the absence of regular physical exertion, and, as a consequence, an increased consumption of non-enzymatic antioxidants. It was found that the early post-sports period is characterized by significantly lower, in comparison with the control group, the values of the activity of the first-order enzymes (superoxide dismutase) against the background of the increased activity of the second-order enzymes (catalase).Conclusions: the obtained data can be recommended for monitoring the state of athletes who stopped playing sports and taken into account when prescribing rehabilitation measures for the corresponding contingent.